A Case Report on Management of Father Daughter Incest with Schizophrenia. (5th December 2016) - Soron, Tanjir Rashid
Abstract : Incest is a neglected and hidden public health problem. This case is about a patient who was victim of sexual abuse, suffered from schizophrenia and abused his biological daughter. He was physically and sexually abused by seniors and classmates, developed paranoid delusion and auditory hallucination. During the course of the illness, he was hospitalized several times as a case of schizophrenia and sexual dysfunction was his main concern. The patient's illness followed a waxing and waning course. He took medication on on-and-off basis. He abused his biological daughter sexually at the later stage of the illness. Ultimately, the patient attempted suicide after an indecent sexual act with another relative and he was admitted to the hospital. He was treated with risperidone that was titrated to 10 mg per day. After continuing the medication for 2 years he regained a functioning life and remained stable with medication. This case shows the importance of exploring the sexual behavior of the patients and sharing the experience may help in the treatment of schizophrenia patients with incest.